Negative electrode active material layer and all-solid battery

The introduction of a halogen-containing solid electrolyte and specifically characterized carbon materials in the negative electrode active material layer addresses the cycling issues of all-solid-state batteries, enhancing both conductivity and reaction stability.

JP2025068236APending Publication Date: 2025-04-28TDK CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023178000
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-16
Publication Date
2025-04-28

AI Technical Summary

Technical Problem

All-solid-state batteries using graphite as the negative electrode active material often deteriorate and fail to achieve sufficient cycling characteristics.

Method used

A negative electrode active material layer is developed, comprising a solid electrolyte with halogen and one or more carbon materials such as graphite, hard carbon, or soft carbon, with specific particle size and orientation characteristics, and optionally including LiCl or sulfur.

Benefits of technology

The proposed solution enhances the cycle characteristics of all-solid-state batteries by improving electron conductivity and suppressing side reactions, resulting in better performance and longevity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025068236000001_ABST
    Figure 2025068236000001_ABST
Patent Text Reader

Abstract

To provide an all-solid battery with an excellent cycle characteristic.SOLUTION: A negative electrode active material layer includes a solid electrolyte and an active material. The solid electrolyte includes halogen. The active material is at least one type of carbon material selected from black lead, hard carbon, and soft carbon. The carbon material is in the shape of a scale or a thin film and the median diameter is at least 2 μm to 4 μm, both inclusive.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a negative electrode active material layer and an all-solid-state battery. [Background technology]

[0002] In recent years, electronics technology has made remarkable progress, with efforts to make portable electronic devices smaller, lighter, thinner, and more multifunctional. This has led to demands for improved performance of the batteries that power these electronic devices.

[0003] Lithium ion secondary batteries are charged and discharged by the active material absorbing and releasing lithium ions. For example, Patent Documents 1 and 2 disclose the use of graphite as the active material.

[0004] In recent years, all-solid-state batteries that use a solid electrolyte as the electrolyte have been attracting attention. Patent Document 3 discloses an all-solid-state battery that uses a sulfide-based solid electrolyte. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 3978802 [Patent Document 2] Patent No. 3683379 [Patent Document 3] International Publication No. 2023 / 112405 Summary of the Invention [Problem to be solved by the invention]

[0006] When graphite is used as the negative electrode active material of an all-solid-state battery, the all-solid-state battery deteriorates and sufficient cycle characteristics may not be obtained.

[0007] The present disclosure has been made in view of the above problems, and has an object to provide a negative electrode active material layer and an all-solid-state battery having excellent cycle characteristics. [Means for solving the problem]

[0008] In order to solve the above problems, the following means are provided.

[0009] (1) A negative electrode active material layer according to a first aspect includes a solid electrolyte and an active material. The solid electrolyte contains a halogen. The active material is one or more carbon materials selected from graphite, hard carbon, and soft carbon. The carbon material is flaky or thin, and has a median diameter of 2 μm or more and 4 μm or less.

[0010] (2) In the negative electrode active material layer according to the above embodiment, the active material may be graphite.

[0011] (3) In the negative electrode active material layer according to the above aspect, the value obtained by dividing the thickness of the carbon material by the length of the major axis of the carbon material may be 0.001 or more and 0.1 or less.

[0012] (4) In the negative electrode active material layer according to the above aspect, the carbon material may be oriented in an in-plane direction perpendicular to the stacking direction.

[0013] (5) In the negative electrode active material layer according to the above embodiment, the halogen may be Cl.

[0014] (6) The negative electrode active material layer according to the above embodiment may further contain LiCl.

[0015] (7) In the negative electrode active material layer according to the above aspect, the mass ratio of LiCl may be 0.1 mass % or more and 1.0 mass % or less.

[0016] (8) In the negative electrode active material layer according to the above aspect, the solid electrolyte may contain elemental sulfur.

[0017] (9) The negative electrode active material layer according to the above embodiment may further contain Li2S.

[0018] (10) In the negative electrode active material layer according to the above aspect, the mass ratio of the Li2S may be 0.1 mass % or more and 1.0 mass % or less.

[0019] (11) An all-solid-state battery according to a second aspect includes a positive electrode, a negative electrode including the negative electrode active material layer according to the above aspect, and a solid electrolyte layer sandwiched between the positive electrode and the negative electrode. Effect of the Invention

[0020] The all-solid-state battery according to the above embodiment has excellent cycle characteristics. [Brief description of the drawings]

[0021] [Figure 1] FIG. 1 is a schematic cross-sectional view of an all-solid-state battery according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view of a negative electrode according to the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] The present embodiment will be described in detail below with reference to the drawings as appropriate. The drawings used in the following description may show characteristic parts in an enlarged scale for the sake of convenience in order to make the features of the present invention easier to understand, and the dimensional ratios of each component may differ from the actual ones. The materials, dimensions, etc. exemplified in the following description are merely examples, and the present invention is not limited thereto, and may be appropriately modified and implemented within the scope of the present invention.

[0023] "All-solid-state battery" FIG. 1 is a schematic cross-sectional view of an all-solid-state battery 100 according to this embodiment. The all-solid-state battery 100 shown in FIG. 1 includes a power generating element 40 and an exterior body 50. The exterior body 50 covers the periphery of the power generating element 40. The power generating element 40 is connected to the outside via a pair of terminals 60, 62 connected to the power generating element 40. Although a laminated type battery is shown in FIG. 1, a wound type battery may also be used. The all-solid-state battery 100 is used, for example, in laminate batteries, square batteries, cylindrical batteries, coin batteries, button batteries, etc.

[0024] <Power generation element> The power generating element 40 includes a solid electrolyte layer 10, a positive electrode 20, and a negative electrode 30. The power generating element 40 is charged or discharged by the exchange of ions between the positive electrode 20 and the negative electrode 30 via the solid electrolyte layer 10 and the exchange of electrons via an external circuit.

[0025] (Negative electrode) As shown in FIG. 1, the negative electrode 30 has a negative electrode current collector 32 and a negative electrode active material layer .

[0026] 2 is a cross-sectional view of the negative electrode 30 according to the first embodiment. Hereinafter, one direction in the plane in which the negative electrode current collector 32 extends is referred to as the x direction, a direction perpendicular to the x direction in the same plane is referred to as the y direction, and a direction perpendicular to the x and y directions is referred to as the z direction. The z direction is an example of a stacking direction. The direction in which the xy plane extends is an example of an in-plane direction.

[0027] The negative electrode current collector 32 extends in the xy plane. The negative electrode current collector 32 may have electronic conductivity. The negative electrode current collector 32 is, for example, a metal such as copper, aluminum, nickel, stainless steel, or iron, or a conductive resin. The negative electrode current collector 32 may be in the form of a powder, a foil, a punching, or an expandable material.

[0028] The negative electrode active material layer 34 is in contact with at least one surface of the negative electrode current collector 32. The negative electrode active material layer 34 is between the negative electrode current collector 32 and the solid electrolyte layer 10. The negative electrode active material layer 34 includes a solid electrolyte 35 and a negative electrode active material 36. The negative electrode active material layer 34 may further include a binder and a conductive assistant as necessary. The solid electrolyte 35 in FIG. 2 is illustrated as being continuous and integrated, but the solid electrolyte particles in the negative electrode active material layer 34 may be densely packed.

[0029] The solid electrolyte 35 is a material that can move ions by applying an electric field from the outside. When the ion conductivity of the solid electrolyte 35 is high, the transfer of ions in the all-solid-state battery 100 becomes smooth, and the internal resistance becomes small. When the stability of the solid electrolyte 35 is high, the initial charge / discharge efficiency of the all-solid-state battery 100 improves. The solid electrolyte 35 is used as a part of the components of the solid electrolyte layer 10, the positive electrode 20, and the negative electrode 30 of the all-solid-state battery 100.

[0030] The solid electrolyte 35 contains a halogen. When the solid electrolyte 35 contains a halogen, the cycle characteristics of the all-solid-state battery 100 are improved. The negative electrode active material 36 according to this embodiment is small, and the contact area between the negative electrode active material 36 and the solid electrolyte 35 is large. In this case, the solid electrolyte 35 and. The risk of the solid electrolyte 35 decomposing due to a side reaction with the negative electrode active material 36 increases. The halogen in the solid electrolyte 35 reacts with lithium to form a coating that protects the solid electrolyte. This coating suppresses the decomposition of the solid electrolyte. In other words, when the solid electrolyte 35 contains a halogen, the decomposition of the solid electrolyte is suppressed, and the cycle characteristics of the all-solid-state battery are improved.

[0031] The solid electrolyte 35 is, for example, Li a E b G c X d It is a halide-based solid electrolyte represented by (1).

[0032] a satisfies 0.5≦a<6, preferably 2.0≦a≦4.0, and more preferably 2.5≦a≦3.5. When E is Zr or Hf, a is preferably 1.0≦a≦3.0, and more preferably 1.5≦a≦2.5. In the compound represented by formula (1), when a is 0.5≦a<6, the content of Li contained in the compound becomes appropriate, and the ionic conductivity of the solid electrolyte 35 becomes high.

[0033] E is an essential component and is at least one element selected from the group consisting of Al, Sc, Y, Zr, Hf, and lanthanoids (La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu). E preferably contains Al, Sc, Y, Zr, Hf, La, and more preferably contains Zr and Y. E improves the ionic conductivity of the solid electrolyte 35. 0 < b < 2. Since the effect of including E can be obtained more effectively, it is preferable that 0.6 ≤ b. Also, E is an element that forms the skeleton of the solid electrolyte 35. It is more preferable that b ≤ 1.

[0034] G is, for example, OH, BO2, BO3, BO4, B3O6, B4O7, CO3, NO3, AlO2, SiO3, SiO4, Si2O7, Si3O9, Si4O 11 、Si6O 18 、PO3, PO4, P2O7, P3O 10 、SO3, SO4, SO5, S2O3, S2O4, S2O5, S2O6, S2O7, S2O8, BF4, PF6, BOB, (COO)2, N, AlCl4, CF3SO3, CH3COO, CF3COO, OOC-(CH2)2-COO, OOC-CH2-COO, OOC-CH(OH)-CH(OH)-COO, OOC-CH(OH)-CH2-COO, C6H5SO3, OOC-CH=CH-COO, OOC-CH=CH-COO, C(OH)(CH2COOH)2COO, AsO4, BiO4, CrO4, MnO4, PtF6, PtCl6, PtBr6, PtI6, SbO4, SeO4, TeO4, HCOO, and is at least one group selected from the group consisting of these. G is preferably at least one group selected from the group consisting of OH, SO4, CH3COO, CF3COO, HCOO, and particularly preferably SO4. When G is included, the potential window on the reduction side of the solid electrolyte 35 becomes wider and it becomes less likely to be reduced.

[0035] c satisfies 0.1 < c ≤ 6. Since the effect of widening the potential window on the reduction side of the solid electrolyte 35 by including G becomes more prominent, it is preferably 0.5 ≤ c. c is preferably c ≤ 3 so that the decrease in the ionic conductivity of the solid electrolyte 35 due to too much G content does not occur.

[0036] X is at least one selected from the group consisting of F, Cl, Br, and I. X is particularly preferably Cl. d satisfies 0 < d ≤ 6.1. d is preferably 1 ≤ d.

[0037] The solid electrolyte 35 is, for example, Li2ZrSO4Cl4, Li2ZrSO4I4, Li2ZrCO3Cl4, Li2Zr((COO)2) 0.5 Cl5, Li2Zr(CH3COO) 0.2 Cl 5.8 , Li2Zr(CF3COO) 0.2 Cl 5.8 , Li2Zr(HCOO) 0.4 Cl 5.6 , Li2ZrBO2Cl5, Li2ZrBF4Cl5, Li3YSO4Cl4, Li3YCO3Cl4, Li3YBO2Cl5, Li3YBF4Cl5.

[0038] Also, the solid electrolyte 35 may contain a sulfur element together with the halogen. The solid electrolyte 35 is, for example, Li 7-x PS 6-x Cl x (x is 1.0 to 1.9) may also be used.

[0039] The negative electrode active material 36 is one or more carbon materials selected from graphite, hard carbon, and soft carbon. Graphite is particularly preferable as the negative electrode active material 36. The negative electrode active material 36 contains Li in a charged state. It can be confirmed by X-ray diffraction that the negative electrode active material 36 contains Li in a charged state. When the negative electrode active material 36 contains Li, the X-ray diffraction peak near 2θ=26° shifts to the low angle side toward near 2θ=24°. When the negative electrode active material 36 contains Li, the color changes from black to gold, so that it can be confirmed by visual inspection whether the negative electrode active material 36 contains Li. When the conductive assistant is also a carbon material, it is possible to distinguish the negative electrode active material 36 from the conductive assistant by checking the presence or absence of Li in a charged state.

[0040] The carbon material is flaky or thin. Flake refers to a shape in which the thickness is sufficiently thin relative to the planar size, for example, the thickness is 1 / 10 or less of the long axis length. The flaky carbon material has a structure in which flaky carbon materials are overlapped, and the layers are easily peeled off, so that the flaky carbon material has lubricity and excellent fluidity. For example, the value obtained by dividing the thickness a by the long axis length b of the negative electrode active material 36 is 0.001 or more and 0.1 or less. The planar shape of the negative electrode active material 36 when viewed from the thickness direction is not particularly limited.

[0041] The negative electrode active material 36 has a median diameter (D50) of 2 μm or more and 4 μm or less. The median diameter of the negative electrode active material 36 is the median diameter of the long axis length b of the negative electrode active material 36. The median diameter of the negative electrode active material 36 can be obtained by extracting a carbon material from the negative electrode active material layer 34 and measuring the particle size distribution. The particle size distribution of the carbon material extracted from the negative electrode active material layer 34 has one peak, and the peak is in the range of 2 μm or more and 4 μm or less. Even when the carbon material contains the negative electrode active material 36 and a conductive assistant, the particle size distribution of the carbon material extracted from the negative electrode active material layer 34 has one peak, and the peak is in the range of 2 μm or more and 4 μm or less.

[0042] The mass ratio of the negative electrode active material 36 in the negative electrode active material layer 34 is, for example, 30 mass% or more, and preferably 50 mass% or more. The mass ratio of the negative electrode active material 36 in the negative electrode active material layer 34 is, for example, preferably 90 mass% or less, and more preferably 60 mass% or less. The reference mass of the negative electrode active material layer 34 is the sum of the masses of the elements constituting the negative electrode active material layer 34 (for example, the negative electrode active material, the solid electrolyte, the conductive assistant, and the binder).

[0043] The negative electrode active material 36 is preferably oriented in the xy-plane direction in the negative electrode active material layer 34. When the negative electrode active material 36 is oriented in the xy-plane direction, the average value of the inclination angle of 100 negative electrode active material particles 36 contained in the negative electrode active material layer 34 with respect to the xy plane is within 15°. When the negative electrode active material 36 is oriented in the in-plane direction, peeling of the interface between the negative electrode active material layer 34 and the negative electrode current collector 32 due to accumulation and expansion of the negative electrode active material 36 during charging and discharging can be suppressed. In addition, the contact between the negative electrode active materials 36 and between the negative electrode active material 36 and the negative electrode current collector 32 becomes surface contact, and the conductive efficiency of the negative electrode 30 is improved.

[0044] The negative electrode active material layer 34 may contain LiCl in addition to the solid electrolyte 35 and the negative electrode active material 36. The mass ratio of LiCl to the total mass of the negative electrode active material layer 34 is, for example, 0.1 mass % or more and 1.0 mass % or less. LiCl adheres to the surface of the solid electrolyte 35 and prevents decomposition of the solid electrolyte 35 during charging and discharging.

[0045] Furthermore, when the solid electrolyte 35 contains elemental sulfur, the negative electrode active material layer 34 may contain Li2S. The mass ratio of Li2S to the total mass of the negative electrode active material layer 34 is, for example, 0.1 mass% or more and 1.0 mass% or less. Li2S adheres to the surface of the solid electrolyte 35 and prevents decomposition of the solid electrolyte 35 during charging and discharging.

[0046] The negative electrode active material layer 34 may contain a binder. The binder bonds the negative electrode active material 36 and the solid electrolyte 35 to each other in the negative electrode active material layer 34, and also firmly bonds the negative electrode active material layer 34 and the negative electrode current collector 32. The negative electrode active material layer 34 preferably contains a binder. The binder preferably has oxidation resistance and good adhesiveness.

[0047] Examples of the binder include polyvinylidene fluoride (PVDF) or its copolymer, polytetrafluoroethylene (PTFE), polyamide (PA), polyimide (PI), polyamideimide (PAI), polybenzimidazole (PBI), polyethersulfone (PES), polyacrylic acid (PA) and its copolymer, metal ion crosslinked polyacrylic acid (PA) and its copolymer, maleic anhydride grafted polypropylene (PP), maleic anhydride grafted polyethylene (PE), or a mixture thereof. Among these, PVDF is particularly preferred as the binder.

[0048] The content of the binder in the negative electrode active material layer 34 is not particularly limited, but is preferably 0.3% by mass to 10% by mass, more preferably 0.3% by mass to 5% by mass, based on the total mass of the negative electrode active material, solid electrolyte, conductive assistant, and binder. If the amount of binder is too small, the adhesive strength of the negative electrode 30 is weakened. Conversely, if the amount of binder is too large, it tends to be difficult to obtain a sufficient volume or mass energy density. This is because the binder is electrochemically inactive and does not contribute to the discharge capacity.

[0049] The conductive assistant improves the electronic conductivity of the negative electrode active material layer 34. The negative electrode active material layer 34 does not need to contain a conductive assistant. Any known conductive assistant can be used. The conductive assistant is, for example, a carbon material such as carbon black, graphite, carbon nanotubes, or graphene; a metal such as aluminum, copper, nickel, stainless steel, iron, or amorphous metal; a conductive oxide such as ITO; or a mixture thereof. The conductive assistant may be in the form of a powder or fiber.

[0050] There is no particular limitation on the content of the conductive assistant in the negative electrode active material layer 34. When the conductive assistant is added, the mass ratio of the conductive assistant is preferably 0.5 mass % or more and 20 mass % or less, and more preferably 1 mass % or more and 5 mass % or less, based on the total mass of the negative electrode active material, the solid electrolyte, the conductive assistant, and the binder.

[0051] (positive electrode) 1, the positive electrode 20 has a plate-shaped (foil-shaped) positive electrode collector 22 and a positive electrode active material layer 24. The positive electrode active material layer 24 is in contact with at least one surface of the positive electrode collector 22.

[0052] The positive electrode current collector 22 may be made of any electronically conductive material that is resistant to oxidation during charging and is not easily corroded. The positive electrode current collector 22 may be made of, for example, a metal such as aluminum, stainless steel, nickel, or titanium, or a conductive resin. The positive electrode current collector 22 may be in the form of a powder, a foil, a punched piece, or an expanded piece.

[0053] The positive electrode active material layer 24 contains a positive electrode active material. The positive electrode active material layer 24 may contain a solid electrolyte, a binder, and a conductive assistant, as necessary.

[0054] The positive electrode active material is not particularly limited as long as it can reversibly absorb and release, and insert and remove (intercalate and deintercalate) lithium ions, and any positive electrode active material used in known all-solid-state batteries can be used. Examples of the positive electrode active material include lithium-containing metal oxides and lithium-containing metal phosphates.

[0055] Lithium-containing metal oxides include, for example, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese spinel (LiMn2O4), and lithium manganese oxides represented by the general formula: LiNi x Co y Mn zO2 (x+y+z=1), lithium vanadium compounds (LiVOPO4, Li3V2(PO4)3), olivine-type LiMPO4 (where M represents at least one selected from Co, Ni, Mn, and Fe), lithium titanate (Li4Ti5O 12 ) etc.

[0056] The positive electrode active material may not contain lithium. Examples of such positive electrode active materials include non-lithium-containing metal oxides (MnO2, V2O5, etc.), non-lithium-containing metal sulfides (MoS2, etc.), and non-lithium-containing fluorides (FeF3, VF3, etc.). When using a positive electrode active material that does not contain lithium, the negative electrode is doped with lithium ions in advance, or a negative electrode containing lithium ions is used.

[0057] The positive electrode active material layer 24 may contain a solid electrolyte. The solid electrolyte is, for example, the solid electrolyte described above. The solid electrolyte contained in the positive electrode active material layer 24 may be the same as or different from the solid electrolyte contained in the negative electrode active material layer 34. When the solid electrolyte material contained in the solid electrolyte layer 10, the positive electrode 20, and the negative electrode 30 is the same, the all-solid-state battery 100 can be easily manufactured.

[0058] The content of the solid electrolyte in the positive electrode active material layer 24 is not particularly limited, but is preferably from 1 mass % to 50 mass %, and more preferably from 5 mass % to 30 mass %, based on the total mass of the positive electrode active material, the solid electrolyte, the conductive assistant, and the binder.

[0059] The binder and conductive assistant contained in the positive electrode 20 are the same as the binder and conductive assistant contained in the negative electrode 30 .

[0060] (solid electrolyte layer) The solid electrolyte layer 10 is sandwiched between a positive electrode 20 and a negative electrode 30. The solid electrolyte layer 10 includes a solid electrolyte that can move ions by an externally applied voltage. For example, the solid electrolyte conducts lithium ions and inhibits the movement of electrons.

[0061] The solid electrolyte layer 10 is, for example, a halide-based solid electrolyte. The solid electrolyte layer 10 includes, for example, the above-mentioned solid electrolyte material. The solid electrolyte included in the solid electrolyte layer 10 may be the above-mentioned one or may be another solid electrolyte.

[0062] The solid electrolyte layer 10 may contain, in addition to the solid electrolyte, a binder, a compound, etc. The binder may be the same as that used in the positive electrode 20 or the negative electrode 30. The compound is a material originating from the raw material powder.

[0063] <Exterior body> The exterior body 50 houses the power generating element 40 therein. The exterior body 50 prevents moisture and the like from entering from the outside to the inside. As shown in Fig. 1, for example, the exterior body 50 has a metal foil 52 and a resin layer 54 laminated on each side of the metal foil 52. The exterior body 50 is a metal laminate film in which the metal foil 52 is coated with the resin layer 54 from both sides.

[0064] The metal foil 52 is, for example, an aluminum foil or a stainless steel foil. The resin layer 54 can be, for example, a resin film such as polypropylene. The materials constituting the resin layer 54 may be different between the inside and outside. For example, the outside material can be a polymer with a high melting point, such as polyethylene terephthalate (PET) or polyamide (PA), and the inside material can be polyethylene (PE) or polypropylene (PP).

[0065] <Terminal> The terminals 60 and 62 are connected to the negative electrode 30 and the positive electrode 20, respectively. The terminal 62 connected to the positive electrode 20 is a positive electrode terminal, and the terminal 60 connected to the negative electrode 30 is a negative electrode terminal. The terminals 60 and 62 are responsible for electrical connection to the outside. The terminals 60 and 62 are made of a conductive material such as aluminum, nickel, or copper. The connection method may be welding or screwing. The terminals 60 and 62 are preferably protected with insulating tape to prevent short circuits.

[0066] [Manufacturing method of all-solid-state batteries] The positive electrode is produced by applying a paste containing a positive electrode active material onto a positive electrode current collector 22 and drying it to form a positive electrode active material layer 24. The above-mentioned solid electrolyte may be added to the paste containing the positive electrode active material.

[0067] Next, the negative electrode 30 is prepared. The negative electrode is manufactured by applying a paste containing a negative electrode active material 36 and a solid electrolyte 35 onto a negative electrode current collector 32, and drying the paste to form a negative electrode active material layer 34. As the negative electrode active material 36, a scaly or flaky carbon material having a median diameter of 2 μm or more and 4 μm or less is prepared. As the solid electrolyte 35, a solid electrolyte containing a halogen is prepared.

[0068] The power generating element 40 can be produced, for example, by powder molding. A guide with a hole is placed on the positive electrode 20, and the guide is filled with a solid electrolyte. The surface of the solid electrolyte is then smoothed, and the negative electrode 30 is placed on top of the solid electrolyte. This sandwiches the solid electrolyte between the positive electrode 20 and the negative electrode 30. Pressure is then applied to the positive electrode 20 and the negative electrode 30 to pressure mold the solid electrolyte. By pressure molding, a laminate is obtained in which the positive electrode 20, the solid electrolyte layer 10, and the negative electrode 30 are stacked in this order.

[0069] Next, external terminals are welded to the positive electrode current collector 22 of the positive electrode 20 and the negative electrode current collector 32 of the negative electrode 30, which form the laminate, by a known method, to electrically connect the positive electrode current collector 22 or the negative electrode current collector 32 to the external terminal. Thereafter, the laminate connected to the external terminal is housed in an exterior body 50, and the opening of the exterior body 50 is heat-sealed to seal it. Through the above steps, the all-solid-state battery 100 of this embodiment is obtained.

[0070] The all-solid-state battery 100 according to this embodiment has excellent cycle characteristics. The negative electrode active material 36 included in the negative electrode 30 of the all-solid-state battery 100 according to this embodiment has a median diameter of 2 μm or more and 4 μm or less, and has a small particle size. When the negative electrode active material layer 34 is filled with the negative electrode active material 36 having a small particle size, the electronic conduction between the negative electrode active materials 36 becomes smooth, and poor contact is unlikely to occur. On the other hand, the negative electrode active material 36 having a small particle size has a risk of easily causing a side reaction with the solid electrolyte 35 because of a large reaction area. By using the solid electrolyte 35 containing a halogen simultaneously with the negative electrode active material 36 having a small particle size, an appropriate protective film can be created and the side reaction of the solid electrolyte 35 can be suppressed. That is, the all-solid-state battery 100 according to this embodiment has excellent cycle characteristics by achieving both good electronic conductivity by using the negative electrode active material 36 having a small particle size and suppression of side reactions by using the solid electrolyte 35 containing a halogen.

[0071] The above describes the embodiments of the present invention in detail with reference to the drawings. However, each configuration and combination thereof in each embodiment is merely an example, and addition, omission, substitution, and other modifications of the configuration are possible without departing from the spirit of the present invention. EXAMPLES

[0072] "Example 1" A full cell of an all-solid-state battery was fabricated, and the discharge capacity and cycle characteristics were measured. The full cell was fabricated in the following manner.

[0073] In a glove box, the container was filled with 80 mg of solid electrolyte and pressed at a pressure of 0.6 tons for 1 minute. The solid electrolyte was LPSC (Li6PS5Cl).

[0074] A negative electrode composite was added to one side of the pressed solid electrolyte, and pressed at a pressure of 0.6 tons for 1 minute, and then pressed at 3 tons for 1 minute. The negative electrode composite contained a negative electrode active material and a solid electrolyte in a ratio of negative electrode active material:solid electrolyte = 60 parts by mass:40 parts by mass. The negative electrode active material was flake graphite with a median diameter of 2.1 μm. The ratio of the major axis length b of the flake graphite to the thickness a was b / a = 0.048. The solid electrolyte contained in the negative electrode composite was LPSC (Li6PS5Cl).

[0075] Next, a positive electrode mixture was added to the surface of the pressed solid electrolyte opposite to the surface on which the negative electrode mixture was laminated, and the mixture was pressed for 1 minute at a pressure of 0.6 tons, and then pressed for 1 minute at 3 tons. The positive electrode mixture contained a positive electrode active material, a solid electrolyte, and a conductive additive in a ratio of 70 parts by mass: 27 parts by mass: 3 parts by mass. The positive electrode active material was lithium cobalt oxide (LiCoO2). The solid electrolyte contained in the positive electrode was LZSOC (Li2SO4Cl4). The conductive additive was carbon black.

[0076] They were restrained at 3 Nm using a restraining jig and sealed in an aluminum pouch with terminals. In this way, a full cell for charge / discharge evaluation was produced.

[0077] The cycle characteristics were measured using a secondary battery charge / discharge tester (manufactured by Hokuto Denko Corporation) in the following manner.

[0078] The cycle characteristics were measured using a CC-CV charge-CC discharge format. Specifically, the battery was first charged at a constant current of 1C at a charge rate up to a maximum charge voltage of 2.7V, and then charged at a constant voltage of 0.5C in constant voltage mode (2.7V). The battery was then discharged at a constant current of 1C at a discharge rate until the battery voltage reached 1.3V. The discharge capacity after the end of the charge and discharge was detected, and the battery capacity Q1 before the cycle test was calculated. This battery capacity Q1 was the initial discharge capacity.

[0079] Next, constant current charging was performed at a charge rate of 1C up to a charging upper limit voltage of 2.7V, and further constant voltage charging was performed up to 0.5C in constant voltage mode (2.7V). After that, discharging was performed at a constant current discharge rate of 1C until the battery voltage reached 1.3V. The above charge and discharge were counted as one cycle, and 100 cycles of charge and discharge were performed. Then, the discharge capacity after the end of charge and discharge was detected, and the battery capacity Q2 after the 100 cycle test was obtained.

[0080] The cycle characteristic is a ratio obtained by dividing the battery capacity Q2 after 100 cycles by the initial battery capacity Q1. The cycle characteristic of Example 1 was 93.6%.

[0081] "Example 2" Example 2 differs from Example 1 in that the shape of the graphite used in the negative electrode active material was changed. Other conditions were the same as in Example 1, and cycle characteristics were determined.

[0082] "Example 3" Example 3 differs from Example 1 in that the negative electrode active material was changed to hard carbon. The shape of the hard carbon was different from that of the graphite in Example 1. The other conditions were the same as in Example 1, and the cycle characteristics were determined.

[0083] "Examples 4 to 7" Examples 4 to 7 differ from Example 2 in that LiCl was added when preparing the negative electrode composite material. The amount of LiCl added differs between Examples 4 to 7. The other conditions were the same as in Example 2, and cycle characteristics were determined.

[0084] "Examples 8 to 11" Examples 8 to 11 differ from Example 3 in that LiCl was added when preparing the negative electrode composite material. The amount of LiCl added differs between Examples 8 to 11. The other conditions were the same as in Example 3, and cycle characteristics were determined.

[0085] "Examples 12 to 15" Examples 12 to 15 differ from Example 2 in that Li2S was added when preparing the negative electrode composite material. The amount of Li2S added differs between Examples 12 to 15. The other conditions were the same as Example 2, and the cycle characteristics were determined.

[0086] "Examples 16 to 19" Examples 16 to 19 differ from Example 3 in that Li2S was added when preparing the negative electrode composite material. The amount of Li2S added differs between Examples 16 to 19. The other conditions were the same as Example 3, and cycle characteristics were determined.

[0087] "Comparative Examples 1 to 3" Comparative Examples 1 to 3 differ from Example 1 in that the shape of the graphite used in the negative electrode active material was changed. Other conditions were the same as in Example 1, and cycle characteristics were determined.

[0088] "Comparative Examples 4 and 5" Comparative Examples 4 and 5 differ from Example 3 in that the shape of the hard carbon used in the negative electrode active material was changed. Other conditions were the same as in Example 3, and cycle characteristics were determined.

[0089] "Comparative Examples 6 to 8" Comparative Examples 6 to 8 differ from Examples 1 to 3 in that the solid electrolyte constituting the negative electrode mixture was changed to LPS (Li6PS6). The other conditions were the same as in Example 1, and cycle characteristics were determined.

[0090] The results of Examples 1 to 19 and Comparative Examples 1 to 8 are summarized in Table 1. As shown in Table 1, the cycle characteristics of the all-solid-state battery were improved by producing the negative electrode active material layer using a fine, flaky carbon material and a solid electrolyte containing a halogen.

[0091] [Table 1]

[0092] "Examples 20 to 22" Examples 20 to 22 differ from Examples 1 to 3 in that the solid electrolyte constituting the negative electrode mixture and the solid electrolyte layer was changed to LZSOC (Li2ZrSO4Cl4). The other conditions were the same as in Example 1, and the cycle characteristics were determined.

[0093] "Examples 23 and 24" Examples 23 and 24 differ from Examples 2 and 3 in that the solid electrolyte constituting the negative electrode composite and the solid electrolyte layer was changed to LZSOI (Li2ZrSO4I4). The other conditions were the same as in Example 1, and the cycle characteristics were obtained.

[0094] "Examples 25 to 29" Examples 25 to 29 differ from Example 21 in that LiCl was added when preparing the negative electrode mixture. The amount of LiCl added differs between Examples 25 to 29. The other conditions were the same as in Example 21, and cycle characteristics were determined.

[0095] "Examples 30 to 32" Examples 30 to 32 differ from Example 21 in that Li2S was added when preparing the negative electrode composite material. The amount of Li2S added differs between Examples 30 to 32. The other conditions were the same as in Example 21, and cycle characteristics were determined.

[0096] "Comparative Examples 9 to 11" Comparative Examples 9 to 11 differ from Example 20 in that the shape of the graphite used in the negative electrode active material was changed. Other conditions were the same as in Example 20, and cycle characteristics were determined.

[0097] "Comparative Examples 12 and 13" Comparative Examples 12 and 13 differ from Example 22 in that the shape of the hard carbon used in the negative electrode active material was changed. Other conditions were the same as in Example 22, and cycle characteristics were determined.

[0098] The results of Examples 20 to 32 and Comparative Examples 9 to 13 are summarized in Table 2. As shown in Table 2, the cycle characteristics of the all-solid-state battery were improved by preparing the negative electrode active material layer using a fine scaly carbon material and a solid electrolyte containing a halogen. As shown in Tables 1 and 2, the solid electrolyte may be a halogen-based solid electrolyte or a sulfide-based solid electrolyte as long as it contains a halogen.

[0099] [Table 2] [Explanation of symbols]

[0100] 10...solid electrolyte layer, 20...positive electrode, 22...positive electrode current collector, 24...positive electrode active material layer, 30...negative electrode, 32...negative electrode current collector, 34...negative electrode active material layer, 35...solid electrolyte, 36...negative electrode active material, 40...power generating element, 50...exterior body, 52...metal foil, 54...resin layer, 60, 62...terminal, 100...all-solid-state battery

Claims

1. A solid electrolyte and an active material are provided. The solid electrolyte contains a halogen, The active material is one or more carbon materials selected from graphite, hard carbon, and soft carbon, The carbon material is flaky or thin and has a median diameter of 2 μm or more and 4 μm or less.

2. The negative electrode active material layer according to claim 1 , wherein the active material is graphite.

3. 2 . The negative electrode active material layer according to claim 1 , wherein a value obtained by dividing the thickness of the carbon material by the length of the major axis of the carbon material is 0.001 or more and 0.1 or less.

4. The negative electrode active material layer according to claim 1 , wherein the carbon material is oriented in an in-plane direction perpendicular to the stacking direction.

5. The negative electrode active material layer according to claim 1 , wherein the halogen is Cl.

6. The negative electrode active material layer according to claim 1 , further comprising LiCl.

7. The negative electrode active material layer according to claim 6 , wherein the mass ratio of the LiCl is 0.1 mass % or more and 1.0 mass % or less.

8. The negative electrode active material layer according to claim 5 , wherein the solid electrolyte contains elemental sulfur.

9. Li 2 The negative electrode active material layer according to claim 8 , further comprising S.

10. The Li 2 The negative electrode active material layer according to claim 9 , wherein a mass ratio of S is 0.1 mass % or more and 1.0 mass % or less.

11. 11. An all-solid-state battery comprising: a positive electrode; a negative electrode including the negative electrode active material layer according to claim 1; and a solid electrolyte layer sandwiched between the positive electrode and the negative electrode.

Citation Information

Patent Citations

  • Graphite for lithium secondary battery negative electrode and method for manufacturing the same

    JP3683379B2

  • Graphite powder suitable for negative electrode materials of lithium secondary batteries

    JP3978802B2

  • Solid electrolyte battery and method for producing solid electrolyte battery

    WO2023112405A1